ANALISIS DAMPAK PELAKSANAAN PROGRAM MBKM TERHADAP TENAGA PENDIDIK DI PRODI PGSD FKIP UNIVERSITAS BUNG HATTA DALAM MENGHASILKAN LULUSAN YANG TANGGUH BERSAING DI ERA GLOBAL - Zulfa Amrina; Arlina Yuza; Syafni Gustina Sari (Program Studi PGSD FKIP Universitas Bung Hatta, 2021)
This article aims to describe the analysis of the impact of the implementation of the MBKM program on Educators at the Bung Hatta University PGSD FKIP Study Program in producing graduates who are tough to compete in the global era. The type of research used is quantitative with a descriptive approach. Data collection techniques using a questionnaire. Data analysis used descriptive statistical techniques, namely data collection, data reduction, data presentation and conclusion drawing. The validity of the data is done by increasing the persistence and triangulation techniques. The results show that 1) Educators (Tendik) know that most of the policy content comes from the Ministry of Education and Culture's online channels (websites/websites, social media) and others from offline/online socialization activities organized by universities. 2) Tendik did not understand the contents of the policy on MBKM because he answered incorrectly the number of credits and semesters of MBKM implementation. 3) Implementation of the MBKM program on improving hard-skills and soft-skills for students is considered by Tendik to be lacking. 4) Tendik is satisfied with the MBKM program, but there are still many obstacles, such as funding, human resource capabilities and regulations.